PENGARUH MODEL ELICITING ACTIVITIES (MEAs) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Muhyani, Muhyani; Elmaknun, Fatimah Mu’jizatiyah; Devi, Abrista (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
This research aims to determine the effect of Model Eliciting Activities (MEAs) on students' mathematical problem-solving abilities. The approach used is a quantitative approach with a nonequivalent control group design quasi-experimental research design. The population in this study consists of second-grade students at Pioneer School Depok, comprising two classes. The sample for this study consists of Class 2B as the experimental group and Class 2A as the control group, selected non-randomly. The experimental group was treated using MEAs, while the control group used conventional models. The research instrument used a descriptive test to measure students' mathematical problem-solving abilities. The data from the mathematical problem-solving ability test were analyzed using an independent sample t-test. The results of the data analysis show that there is a significant effect of MEAs on mathematical problem-solving abilities.